Quantum mechanics for nuclear structure. a primer - Heyde, Kris L. G., 1942-; Wood, J. L. (John L.), 1941- (IOP ebooks. 2020 collection., 2020)
This book, the first of a two-volume set, provides a comprehensive introduction to quantum mechanics for advanced undergraduate and postgraduate students entering the field of nuclear structure studies via two-state systems: both polarized photons and spin-1/2 particles. This leads to the logic behind the physical structure and an axiomatic formulation using linear spaces and operators. The one-dimensional harmonic oscillator is used to illustrate the mechanics of quantized systems, reaching to time dependence and coherent states. Measurement theory is introduced. The transformation theory of space and time leads to wave functions. The role of group theory and rotations then leads to the quantization of angular momentum. Central force problems are handled algebraically. The development is completed with quantization of motion of a charged particle in a magnetic field. Part of IOP Series in Nuclear Spectroscopy and Nuclear Structure.